Data structure for radial distribution system load flow analysis - Venkatesh, B.; Ranjan, R. (2003)
Owing to the radial nature and high R/X ratio, radial distribution systems (RDS) employ a special recursive technique for distribution load flow (DLF). An efficient method for DLF plays a critical role in automation algorithms of RDS whose scope encompasses fault isolation, network reconfiguration and service restoration. The ability of automation algorithms to handle these complex tasks that require frequent topology changes in the RDS demands a dynamic topology processor based on a well-defined data structure. The purpose of this paper is to formulate a dynamic data structure (DDS) and an algorithm that generates the DDS of the RDS as an R-tree. The proposed DDS algorithm generates the DDS and is used as a topology processor in the DLF algorithm. The resulting DLF algorithm is computationally efficient and can handle rapidly changing topology by updating the R-tree. The pseudocodes for the DDS algorithm and the overall recursive algorithm for DLF are presented. Various RDS have been tested with the proposed method and the results demonstrate its efficiency over other known methods of DLF.